Encyclopedia of environmetrics - El-Shaarawi, A. H.; Piegorsch, Walter W. (Wiley, 2012)
An expanded and revised edition of an essential reference work for university libraries, research laboratories, government institutions and consultancies concerned with the environmental sciences -- Provided by publisher.